2004
DOI: 10.1128/jcm.42.4.1794-1796.2004
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Commercial, Type-Specific Enzyme-Linked Immunosorbent Assay for Detection of Herpes Simplex Virus Type 2-Specific Antibodies in Ugandans

Abstract: Two hundred forty-eight human immunodeficiency virus (HIV)-positive and 496 HIV-negative subjects in Uganda were tested by HerpeSelect herpes simplex virus type 2 enzyme-linked immunosorbent assay (ELISA) and Western blotting to optimize the ELISA for use in this population. A higher index cutoff value was required for optimal sensitivity and specificity, and overall performance of the assay was not affected by HIV status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 13 publications
3
55
2
Order By: Relevance
“…Positively selected amino acid residues were frequently identi- fied in HSV glycoproteins, with the highest number of positively selected sites occurring in gC-1 and gG-2. This finding, along with the detection of five or more positively selected sites in gG-2 and a high number of nonsynonymous substitutions, was an indication that perhaps nucleotide variation and the resulting antigenic variation were impacting the sensitivity or specificity of the Western blot assay in East Africa, where there is a significant difference between ELISA and Western blot results (25)(26)(27)(28). This may be due in part to the U.S. strain of HSV-2 used to provide the antigens in the Western blot and extends to the antigen used in commercial ELISAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positively selected amino acid residues were frequently identi- fied in HSV glycoproteins, with the highest number of positively selected sites occurring in gC-1 and gG-2. This finding, along with the detection of five or more positively selected sites in gG-2 and a high number of nonsynonymous substitutions, was an indication that perhaps nucleotide variation and the resulting antigenic variation were impacting the sensitivity or specificity of the Western blot assay in East Africa, where there is a significant difference between ELISA and Western blot results (25)(26)(27)(28). This may be due in part to the U.S. strain of HSV-2 used to provide the antigens in the Western blot and extends to the antigen used in commercial ELISAs.…”
Section: Discussionmentioning
confidence: 99%
“…Because serology tests used to discriminate HSV-1 and HSV-2 infections are frequently inaccurate in East African populations (25)(26)(27)(28), we further examined HSV-2 gG amino acid sequences using phylogenetic methods. The analysis demonstrated that most global strains were dispersed around the tree, with few clusters with bootstrap support greater than 50%; however, there was one large (14 sequences), low-diversity clade (Ͻ0.1%) with moderate bootstrap support (Ͼ60%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the FDAapproved and widely available HerpeSelect enzyme-linked immunosorbent assay (ELISA) (Focus Technologies) has a high sensitivity and specificity, ranging from 96 to 100%, against the reference HSV-2 Western blot (WB) assay for testing of sera from North American or Western European populations but significantly lower specificity for testing of sera from adult African populations (2,7,16). Moreover, concordance between WB and HerpeSelect assays was found to vary between countries in sub-Saharan Africa (2,6,7,9) and according to human immunodeficiency virus (HIV) serostatus (16). HerpeSelect and other assays were compared in an evaluation study using African sera from population-based surveys, and the Kalon gG2-specific ELISA (Kalon Biologicals) was found to be as sensitive as and more specific than HerpeSelect, with WB as the reference method (16).…”
mentioning
confidence: 99%
“…The results are reported according to their antibody index (AI), with values of Ͻ0.9 considered negative, 0.9 to 1.0 equivocal, and Ͼ1.0 positive. Serum samples were tested in parallel using the HerpeSelect gG2 ELISA, and the results were expressed using AIs of 1.1, as recommended by the manufacturer, and 3.5, as recommended by many authors to improve the assay's specificity in African individuals (4,6,7,9,15). The kappa statistic was used to assess the concordance between the two assays.…”
mentioning
confidence: 99%